2021
DOI: 10.1108/ejim-08-2021-0435
|View full text |Cite
|
Sign up to set email alerts
|

University business idea incubation and stakeholders' engagement: closing the gap between theory and practice

Abstract: PurposeThe paper aims to contributes on the debates about University Idea Incubation by investigating the role and the engagement of different University's stakeholders in the process of opportunity recognition in an entrepreneurship education program targeted at students with an interdisciplinary background.Design/methodology/approachThrough a longitudinal case study methodology, the Contamination Lab at University of Salento (Lecce, Italy), the learning approaches and the knowledge process to create an entre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 101 publications
1
7
0
1
Order By: Relevance
“…These study findings align with some previous studies by (Dahlstrand & Berggren, 2010;Lerro & Schiuma, 2022;Mgaiwa, 2021;Secundo, Mele, Passiante, & Albergo, 2021) which suggested that incubation and innovation hubs should be established for the sake of creating and developing entrepreneur mind-sets among students while considering its configuration with respect to the market requirements, innovation, leverage of technology, shifting of training practices, and fully engagement of key stakeholders.…”
Section: Qualitative Data Collection and Analysissupporting
confidence: 90%
“…These study findings align with some previous studies by (Dahlstrand & Berggren, 2010;Lerro & Schiuma, 2022;Mgaiwa, 2021;Secundo, Mele, Passiante, & Albergo, 2021) which suggested that incubation and innovation hubs should be established for the sake of creating and developing entrepreneur mind-sets among students while considering its configuration with respect to the market requirements, innovation, leverage of technology, shifting of training practices, and fully engagement of key stakeholders.…”
Section: Qualitative Data Collection and Analysissupporting
confidence: 90%
“…As the entrepreneurship process can be subdivided into numerous partial tasks, these could also be used as entrepreneurial subprojects. For example, students could work on brand name and logo development, business idea development (Secundo et al 2023), business model development (Bolzani and Luppi 2021;Hasche and Linton 2021;Snihur et al 2021), company registration, entrepreneurial marketing (Amjad et al 2020; Thanasi-Boçe 2020), (minimum viable) product/service development (White and Kennedy 2022; Wu and Chen 2021), etc. Apart from subdividing the whole entrepreneurship process into partial projects, a more demanding approach, for both students and instructors, is to undergo the whole process from idea to market.…”
Section: Discussionmentioning
confidence: 99%
“…Laboratorium bisnis digital juga memberikan lingkungan yang kolaboratif dan inovatif di mana mahasiswa dapat berinteraksi dengan sesama mahasiswa, dosen, dan profesional bisnis (Shih & Aaboen, 2019). Menurut (Secundo et al, 2021) kolaborasi ini dapat meningkatkan pertukaran ide, pembelajaran, dan pengembangan jaringan bisnis yang berharga bagi mahasiswa.…”
Section: Pendahuluanunclassified